Early Diagnosis and Prognosis of Hereditary Breast Cancer - Baxramova Gulzirabonu; Djalolova Feruza (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
Hereditary breast cancer (HBC), driven by highly penetrant mutations in genes like BRCA1/2, TP53, and PALB2, represents an aggressive oncological subset. This review highlights the necessary paradigm shift from generalized screening to individualized, genetically-guided surveillance. The integration of high-resolution MRI and next-generation sequencing (NGS) has transformed early detection, identifying micro-malignancies long before mammographic visibility. Furthermore, targeted pharmacotherapies, notably PARP inhibitors exploiting homologous recombination deficiency (HRD), have radically redefined HBC prognosis. Ultimately, integrating precision oncology and comprehensive genetic counseling is imperative to mitigate phenotypic risks and optimize long-term survivorship.